Transmission of Knowledge from Practice to Theory as a Direct Agency for Social Intervention and an Active and Integral Part of Situational Learning - Lebaka, Morakeng Edward Kenneth (Current Progress in Arts and Social Studies Research Vol. 4, 2024)
This chapter discusses learning from practice to theory as the most effective mode of knowledge transfer. This is in tandem with the axiom: ‘You keep on listening, you are likely to forget, but you keep on doing, you will never forget’. This simply implies that practical knowledge is more important than theoretical knowledge. The fact is that theory assists researchers and teachers with a clearer understanding of a research problem; and critically reflects on education policy and classroom practice, but that does not necessarily mean that theoretical knowledge should be more important than practical knowledge. It has emerged from this study that learning should be self-directed; meaning, students should have some choice in what and how to learn. During interviews, it was also established that practical work promotes experiential learning, encourages self-learning, leads to perfection, and makes students independent and increases their confidence. The impression created during interviews was that the transmission of knowledge in academia can be seen as taking place through oral form (word of mouth). Speech is normally an organized use of words in spoken language to communicate the modes for skills’ transference; however, it would appear that some Creative Arts educators have evolved sophisticated systems, while others may be more ephemerally, oral and non-verbally held within the communal system of mores, codes and conventions, to be substantiated, confirmed and reconfirmed in practical and appropriate situations. Closer investigation has shown that we need a fast and lasting solution to our academic challenge. Further research will shed light on how learning is realized in practice. Drawing on the preceding observations, one is still inclined to argue that theory and practice are inextricably interrelated, but practice should be more important than theory. Based on the findings of this study, it is envisaged that this study will add value to the scientific community as it supports the practical transformation of knowledge, which is essential in modern teaching practice.